PERSEPSI GURU TENTANG SUPERVISI AKADEMIK KEPALA MADRASAH HUBUNGANNYA DENGAN KINERJA GURU - Jahari, Jaja; Sri Lestari, Ambar; Kiki, Deden (Jurnal Inovatif Manajemen Pendidikan Islam, 2022)
This research is motivated by the author's interest in teachers' perceptions about the academic supervision of madrasah principals because in general these perceptions have not been conveyed equally. With teachers' insensitivity to the academic supervision of madrasah principals, teachers are still felt indifferent to the quality of their performance. The task and responsibility of the teacher is to provide learning in accordance with predetermined learning objectives. However, the word appropriate is not enough, teachers are required to improve the quality of their performance with all existing abilities. With teachers' perceptions of evenly distributed academic supervision, it will increase the potential and quality of teacher performance in learning. This study is based on a theory about teachers' perceptions of academic supervision carried out by madrasah principals and teacher performance in learning. This theory will directly influence teacher behavior in helping student learning to achieve organizational goals in the sense of improving teacher performance in learning. This research uses a quantitative approach with descriptive correlational methods. Data obtained by distributing questionnaires (questionnaires), observation and documentation. In data analysis techniques, researchers used test instruments, namely validity test (variable X 27 is valid and variable Y 30 is valid) and reliability (variables X and Y are all reliable), partial analysis of indicators (variable X value is 3.95 high category and variable value Y 4.30 high category), data normality test (variable X 0.2 is normally distributed and variable Y 0.185 is normally distributed), data linearity test (0.064> 0.05 both linear variables) and correlation analysis (0.590 both variables are moderately correlated). It can be concluded that the two variables are one-way, thus it can be interpreted that the increase in teacher perceptions about the academic supervision of madrasah principals will increase the performance of teachers in learning. .